KOMUNIKASI INTERPERSONAL MAHASISWA DAN DOSEN PEMBIMBING DALAM MENYELESAIKAN BIMBINGAN SKRIPSI (Studi Pada Mahasiswa Prodi Ilmu Komunikasi Angkatan 2020 FISIP UIN Raden Fatah Palembang) - Ariza Melinda; Eraskaita Ginting; M. Arif Setiawan (Jurnal Ilmiah Ilmu Komunikasi Communique, 2026)
This study aims to analyze interpersonal communication between students and their supervisors during the thesis guidance process. This study uses symbolic interaction theory, which views that meaning in communication is formed through social interaction and interpretation of symbols that emerge during the guidance process. The method used is a qualitative approach with data collection techniques through in-depth interviews and observations of students from the class of 2020 and their supervisors. The results show that interpersonal communication during thesis guidance occurs through verbal and nonverbal communication. Verbal communication is evident in students' ability to ask questions, explain revisions, and respond to lecturer feedback systematically. Meanwhile, nonverbal communication is reflected through facial expressions, eye contact, gestures, and tone of voice that influence the atmosphere of the interaction. The interactions that occur show the development of students' attitudes from anxiety to confidence during the guidance process. This study also found several obstacles in thesis guidance, such as academic unpreparedness, psychological anxiety, time constraints, and decreased motivation to make revisions. Overall, symbolic interaction between students and their supervisors forms a shared understanding that supports the smooth completion of the thesis.